Therapeutic impact of dietary ginger supplementation in chickens experimentally infected with coccidia—anti-oxidant, biochemical, and pathological evaluations - Saber, Alshimaa; Mawas, Amany Sayed; Khalil, Atef M.; Ahmed, Ahmed I.; Shibat Elhamd, Dina M. W.; Ali, Esraa; Rehan, Ibrahim F.; Elnagar, Asmaa; Zigo, František; Salah, Mohammed (Frontiers in Veterinary Science, 2025)
Coccidiosis is a significant disease with economic implications. It causes high mortality and morbidity, often associated with weight loss. This study investigated the effects of ginger supplementation on antioxidant status, biochemical parameters, and intestinal tissue histopathology in experimentally induced coccidiosis. One hundred one-day-old broiler chicks (Ross) were purchased from a local hatchery. Birds were kept in a clean, well ventilated and disinfected shed. The birds were given non-pelleted diets and water ad libitum throughout the period of the study (25 days). The aqueous ginger was administered orally to the chicks of the four dietary groups via drinking water at concentrations of 6 gm/L of water. All biosecurity measures were adopted according to standard protocol. The chicks were allocated into five groups: control negative (CN), control positive (CP) was infected with 3 × 104 sporulated oocysts at day 14th of the experiment, the third group (GO) was given ginger only for 25 days, the fourth group (GB) was given ginger from day 4th to day 25th of the experiment, and the fifth group (GA) was given ginger from day 5th post infection to day 25th of the experiment. Ginger extract treatment reduced the fecal oocyst count in the infected group, particularly on day 10 post-infection. The alterations in differential leukocyte counts due to coccidial infection were ameliorated by ginger extract administration. Biochemically, compared to the infected group, ginger (Zingiber officinale) reversed the altered biochemical parameters (total protein, albumin, MDA, and SOD enzyme) associated with cecal coccidiosis. Immunologically, ginger extract treatment increased CD4 T cell counts and overexpression of INF-γ in the cecal epithelium. Histological examination revealed a significant reduction in goblet cell number and a decrease in the villus height (VH) to crypt depth (CD) ratio in infected chicks. Restoration of normal cecal histological structure and increased absorptive function and goblet cell number were observed in ginger-treated chicks compared to control-positive chicks. In conclusion, ginger supplements have effective therapeutic uses against intestinal coccidiosis as shown in the biochemical, immunohistochemical and histopathological results.